Does team telecommuting affect productivity? An experiment - E. Glenn Dutcher; Krista Jabs Saral (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
Telecommuting policies have been increasingly adopted by employers. The benefits of telecommuting from the employer's perspective include direct cost-saving from not having to house employees in an office and indirect cost-saving through reduced turnover associated with increased employee satisfaction. The downside is the perceived opportunity for shirking outside of the traditional workplace, a problem which is potentially exacerbated if employees are placed into telecommuting teams. Using a controlled experiment which randomly assigned subjects to participate in the laboratory (non-telecommuters) or to participate online in a location of their choice (telecommuters), we directly test whether telecommuters are more likely to free ride when in teams and whether or not the locational composition of the team influences this outcome. We find no evidence of free-riding in teams for either telecommuters or non-telecommuters. We also find that variation in output when a worker is paired in a traditional team versus a telecommuting team can be attributed to the beliefs subjects have about their teammates' productivity. The last result leads directly to policy implications for managers.
Keywords: J21; J24; J28; C90; 330; Telecommuting; Team Production; Productivity; Virtual Teams; Economic Experiments